Pengembang modul berbasis Problem Based Learning (PBL) terintegrasi literasi sains pada materi laju reaksi kimia - Hanna Grace Sembiring; Ani Sutiani (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research is a type of Research and Development (R&D) research that aims to develop a problembased learning (PBL) module integrated with science literacy on reaction rate materials. The subject of this study is an integrated PBL-based module of science literacy. The object of this study is the material of the Chemical Reaction Rate. This study refers to the steps, Borg and Gall but is limited to 5 steps or stages. The steps begin with data and information collection, PBL-based module development planning, initial product development, initial field trials, and revision of trial results. The modules that have been developed are validated by 3 material expert validators and 3 media expert validators. Then, the module was tested on 2 teachers and class XI-IPA 2 students totaling 30 students of SMA Negeri 7 Medan. Meanwhile, to see the attractiveness of the module, a data collection method was carried out using a research instrument in the form of a questionnaire. The results showed that the PBL-based module integrated science literacy on chemical reaction rate materials declared eligible after validation by obtaining an average percentage of material experts of 84.63% with a valid / feasible category and an average percentage of media experts of 84.41% with a valid / feasible category. And it was declared interesting after obtaining an average percentage of teacher responses of 93.45% with a very interesting category and an average percentage of student responses of 86.77% with a very interesting category.